Pengaruh Imbangan Minyak Ikan Lemuru dan Minyak Kelapa Sawit terhadap Karkas dan Komposisi Kimia Daging Ayam Broiler: Effect of Balancing Lemuru Fish Oil and Palm Oil on Carcass and Chemical Composition of Broiler Chicken Meat - Rizky Nadia; Widya Hermana; Dwi Margi Suci (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
The purpose of this research was to analyze effect of the balancing lemuru fish oil and palm oil on the carcass of broiler and chemical composition of breast of broiler. 200 broilers reared from DOC to 35 days old. Broilers were divided into 4 treatment groups and 5 replications. The treatment consisted of: P0 = diet with 3% crude palm oil, P1 = diet with 1% lemuru fish oil + 2% crude palm oil, P2 = diet with 2% lemuru fish oil + 1% crude palm oil, P3 = diet with 3% lemuru fish oil. Data were analyzed using ANOVA with Duncan's significant difference test. Treatment with lemuru fish oil up to 3% had significant effect (P<0.05) on decreasing carcass but increasing the proportion of thigh. The use of lemuru fish oil feed as much as 2% and palm oil as much as 1% is more effective than control diet on carcass and meat chemistry composition.